Assessment of Running Safety of Developed Train–Bridge–Wave Model Under One-Direction and Two Bidirectional High-Speed Train Passing Subjected to Rail Irregularities. Issue 2 (February 2023) - Razzaghi Kalajahi, Amin; Esmaeili, Morteza; Ali Zakeri, Jabbar
A study about the running safety of trains moving over bridges subjected to hydrodynamic loads under one-direction and two bidirectional high-speed train passing is presented. Dynamic performance of the developed 3D train–bridge–wave system (TBW model) subjected to different hydrodynamic loads and applying Association of American Railroads track irregularities is established in this study. The dynamic responses of the bridge, which is under one-direction and two bidirectional high-speed train passing and subjected to several hydrodynamic loads and rail irregularities, are analyzed. The dynamic responses of the bridge and the running safety indices of the trains on the bridge under several types of sea states in one-direction and two bidirectional train passing are analyzed. Results of developed TBW's sensitivity analyses have shown the importance of sea-state conditions for safe train running. Irregularities have an obvious effect on the dynamic responses of the bridge. Between comparing one-direction and two bidirectional high-speed train passing modes, bidirectional train passing has a greater effect on vertical acceleration and displacement than horizontal ones in the presence of a hydrodynamic load. Therefore, the combination of wave forces, rail irregularities, and bidirectional train passing jeopardizes the running safety of high-speed trains by increasing both lateral and vertical displacements and accelerations. Furthermore, the effect of wave force on the running safety indices of the train is investigated by considering different train speeds. As expected, the tendency observed in all the derailment criteria is similar, indicating that the risk of derailment increases with the increasing of the running speed and wave height.